Effects of Organizational Atmosphere and Organizational Practice on Knowledge, Attitude, and Practice Toward Diffusion and Utilization of Hepatic Contrast-Enhanced Ultrasound Among Physicians - Lu, Junhong; Deng, Qingwen; Liu, Wenbin (Frontiers in Public Health, 2022)
Background Promoting technology diffusion and utilization is a key measure to address the great disparity in technical capacity within integrated health systems. However, even the effectiveness and appropriateness regarding technology has been widely recognized, its diffusion and utilization are still stagnant. The mechanisms that influence the technology from being recognized to being widely applied in practice remain largely unknown. Purpose Taking hepatic contrast-enhanced ultrasound (CEUS) as an example, this study aimed to investigate the comprehensive influencing mechanism of organizational atmosphere and organizational practice on the knowledge, attitude, and practice toward diffusion and utilization of hepatic CEUS in the medical alliance. Methods Based on the integration of organizational ready for change (ORC) and knowledge-attitude-practice (KAP), a structured questionnaire was developed. A multistage random sampling method was applied to investigate physicians who directly use CEUS working at the liver disease-related departments of sampled health institutions. Structural equation modeling (SEM) was used to verify the proposed hypotheses, and determine the relationship between the factors. Results In total, 292 physicians were included. SEM results demonstrated that knowledge influenced both attitude and practice, while attitude positively predicted practice. Organizational practice and organizational atmosphere associated positively with each other. Organizational atmosphere positively affected the physicians' attitude toward CEUS diffusion and utilization (β = 0.425, p < 0.001), while organizational practice positively affected corresponding knowledge (β = 0.423, p < 0.001) and practice (β = 0.275, p < 0.001). Additionally, there was a partial mediating effect between organizational practice and physicians' CEUS diffusion and utilization behavior. Conclusion By verifying the influencing mechanism of organizational atmosphere and organizational practice on the physicians' KAP of hepatic CEUS diffusion and utilization, this study benefit tailoring strategies for promoting technology diffusion and utilization within medical alliance. It is recommended to develop an organizational atmosphere of advocating technology innovation, establish organizational support mechanism (SM) with multiple concrete supporting countermeasures, and so on.